Investigating the role of phosphatases in the regulation of mitosis - Leitch, I (2024)
The equal segregation of sister chromatids into progeny cells during mitosis is essential for preserving genomic integrity and supporting normal cellular functions across generations. Many aspects of mitosis including the spindle assembly checkpoint (SAC), the anaphase promoting complex/cyclosome (APC/C) and formation of stable kinetochore-microtubule attachments are regulated by dynamic and reversible phosphorylation reactions carried out by kinases and phosphatases. Protein phosphatase 1 (PP1), of which there are three catalytic isoforms in mammalian cells, is essential for control of mammalian cell division and has been implicated in the control of the SAC, the APC/C and kinetochore-microtubule attachment formation. However, its precise roles during mitosis are not yet fully understood, especially the potential of distinct isoform specific functions. This thesis explores the effect of an acute PP1 degradation of the mitosis-associated PP1a and PP1g catalytic isoforms to analyse cell cycle progression in the absence of PP1. Concurrent acute degradation of PP1a and PP1g results in delayed chromosome alignment as well as a delay at the metaphase to anaphase transition. During chromosome congression, there is an increase in the frequency of polar localised chromosomes in the absence of PP1 which leads to prolonged SAC signalling. Biochemically overriding the SAC alleviates the chromosome alignment, but not the anaphase onset delay, suggesting that PP1 has SAC-dependent and independent functions in mitosis. The proposed phospho-regulation of the SAC protein p31comet is also explored as a potential PP1 substrate for timely anaphase onset.